10‐year survival rate and the incidence of peri‐implant disease of 374 titanium dental implants with a SLA surface: a prospective cohort study in 177 fully and partially edentulous patients. Issue 10 (5th November 2014) - van Velzen, Frank J.J.; Ofec, Ronen; Schulten, Engelbert A.J.M.; ten Bruggenkate, Christiaan M.
Abstract Purpose This prospective cohort study evaluates the 10‐year survival and incidence of peri‐implant disease at implant and patient level of sandblasted, large grid, and acid‐etched titanium dental implants (Straumann, soft tissue level, SLA surface) in fully and partially edentulous patients. Material and methods Patients who had dental implant surgery in the period between November 1997 and June 2001, with a follow‐up of at least 10 years, were investigated for clinical and radiological examination. Among the 506 inserted dental implants in 250 patients, 10‐year data regarding the outcome of implants were available for 374 dental implants in 177 patients. In the current study, peri‐implantitis was defined as advanced bone loss (≧1.5 mm. postloading) in combination with bleeding on probing. Results At 10‐year follow‐up, only one implant was lost (0.3%) 2 months after implant surgery due to insufficient osseointegration. The average bone loss at 10 year postloading was 0.52 mm. Advanced bone loss at 10‐year follow‐up was present in 35 dental implants (9.8%). Seven percent of the observed dental implants showed bleeding on probing in combination with advanced bone loss and 4.2% when setting the threshold for advanced bone loss at 2.0 mm. Advanced bone loss without bleeding on probing was present in 2.8% of all implants. Conclusion In this prospective study, the 10‐year survival rate at implant and patient level was 99.7% and 99.4%, respectively. Peri‐implantitis was present in 7% of the observed dental implants according to the above‐mentioned definition of peri‐implantitis. This study shows that SLA implants offer predictable long‐term results as support in the treatment of fully and partially edentulous patients.